2014
DOI: 10.1002/2013ja019175
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale ionospheric flow and aurora precursors of auroral substorms: Coordinated SuperDARN and IMAGE/WIC observations

Abstract: We use global-scale polar cap flow vector measurements from the Super Dual Auroral Radar Network (SuperDARN) with the concurrent auroral observations from the Wideband Imaging Camera on board Imager for Magnetopause-to-Aurora Global Exploration (IMAGE/WIC) to study the polar cap flow and auroral precursors during a substorm onset on 26 December 2000. We show, for the first time, close connection between the dayside and nightside polar cap flow enhancements (with the enhanced dayside flow preceding the nightsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The modelling work by Ohtani et al (2018), Ohtani and Yoshikawa (2016) seeks to address some of these issues by considering the interaction of plasma vortices with conductivity gradients in the ionosphere, it ignores any reconnection processes occurring in the magnetosphere. Observational studies have also shown the occurrence of dayside and nightside flow enhancements in concert with the onset of PBIs (Shi and Zesta 2014). However, the causal link between these events is yet to be conclusively demonstrated.…”
Section: Implications and Outstanding Issuesmentioning
confidence: 99%
“…The modelling work by Ohtani et al (2018), Ohtani and Yoshikawa (2016) seeks to address some of these issues by considering the interaction of plasma vortices with conductivity gradients in the ionosphere, it ignores any reconnection processes occurring in the magnetosphere. Observational studies have also shown the occurrence of dayside and nightside flow enhancements in concert with the onset of PBIs (Shi and Zesta 2014). However, the causal link between these events is yet to be conclusively demonstrated.…”
Section: Implications and Outstanding Issuesmentioning
confidence: 99%
“…In the nightside ionosphere, patches convect into the nightside auroral oval under the influence of tail reconnection. Patches convecting into the auroral oval have been shown to be associated with substorm onset [Lyons et al, 2011;Nishimura et al, 2013Nishimura et al, , 2014Shi and Zesta, 2014]. In the auroral oval, they are termed auroral blobs [Tsunoda, 1988;Crowley et al, 2000;Lorentzen et al, 2004;Pryse et al, 2006].…”
Section: Polar Cap Patch Activitymentioning
confidence: 99%
“…However, recent studies based on radar measurements have revealed mesoscale convection features in the polar cap that are of great importance for triggering nightside auroral intensifications [de la Beaujardière et al, 1994;Nishimura et al, 2010;Lyons et al, 2011;Shi et al, 2012;Pitkänen et al, 2013;Shi and Zesta, 2014]. The observed flow features are of~0.2 h magnetic local time (MLT) wide and have larger velocity than slow, uniform surrounding flows, appearing as channels of velocity enhancements.…”
Section: Introductionmentioning
confidence: 99%